KUALITAS PRODUK DAN PROMOSI DALAM MEMPENGARUHI KEPUTUSAN KONSUMEN MENGGUNAKAN JASA PENYEWAAN PRODUK ALAT BERAT: STUDI KASUS PADA PT.SURYA TRIAS GEMILANG - Fikri Firdaus; Sugiharto Sugiharto; Bambang Karnain; Tjandra Wasesa; Achmad Daengs GS (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to examine and analyze the effect of quality products and promotions on consumer decisions in using services rental of heavy equipment products at PT. Surya Trias Gemilang Surabaya. Study this is implemented at PT. Surya Trias Gemilang Surabaya in April Until June 2021. The research population is consumers who have used the service rental of heavy equipment products. Samples were taken as many as 35 people with random sampling technique. Data was collected using valid questionnaire. The dependent variable in this study is the decision consumers (Y), while the independent variables are product quality (X1) and promotion (X2). Data analysis was performed using multiple linear regression method. The results showed that: (1) there was a significant effect of product quality (X1) on consumer decisions (Y) in using tenant services heavy equipment products at PT. Surya Trias Gemilang Surabaya; (2) there is an effect significant promotion (X2) on consumer decisions (Y) in using heavy equipment product rental services at PT. Surya Trias Gemilang Surabaya; and (3) there is a significant effect of product quality and promotion on decisions consumers in using heavy equipment product rental services at PT. Sun Trias Gemilang Surabaya. Product quality factor (X1) and promotion (X2) has an influence of 68.9% on consumer decisions (Y) in use the services of renting heavy equipment products at PT. Surya Trias Gemilang Surabaya, while the remaining 31.1% is influenced by other variables that are not included in this study.